2017
DOI: 10.1186/s40880-016-0171-6
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent chemoradiotherapy combined with enteral nutrition support: a radical treatment strategy for esophageal squamous cell carcinoma patients with malignant fistulae

Abstract: BackgroundConcurrent chemoradiotherapy (CCRT) significantly increases the survival rate of esophageal squamous cell carcinoma (ESCC) patients with malignant fistulae. Recent clinical evidence has shown the benefits of enteral nutrition for malnourished cancer patients. In this study, we aimed to validate that, with the support of enteral nutrition, ESCC patients who develop malignant fistulae might be able to complete CCRT and achieve long-term survival.MethodsWe reviewed the medical records of 652 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Nutritional status has been closely linked to cancer mortality. 7 , 8 Recently, studies have proved that several nutrition-based indices, such as the prognostic nutritional index (PNI), body mass index (BMI), serum albumin, and preoperative body weight loss, have important prognostic value across varied malignancies, including GC. 9 12 A study of 1,249 cases from Chen et al found that a low BMI might be associated with poorer survival among patients with stage III–IV GC.…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional status has been closely linked to cancer mortality. 7 , 8 Recently, studies have proved that several nutrition-based indices, such as the prognostic nutritional index (PNI), body mass index (BMI), serum albumin, and preoperative body weight loss, have important prognostic value across varied malignancies, including GC. 9 12 A study of 1,249 cases from Chen et al found that a low BMI might be associated with poorer survival among patients with stage III–IV GC.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to tumor behavior and inflammation, the patient's nutritional status also has been closely linked to cancer prognosis. [ 17 ] Moreover, the presence of systemic inflammation is proposed to be pathogenic in the development of cancer-related malnutrition. [ 18 ] Nutritional impairment in turn is correlated with poor immunological functions, and shorter survival.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that cancer-related malnutrition is a common but often unrecognized problem[ 47 ], and the prognosis of cancer is closely linked to nutritional status[ 48 - 50 ]. Several potential mechanisms have been hypothesized for their relationship.…”
Section: Discussionmentioning
confidence: 99%